THE GIST OF DIGITAL TECHNOLOGY FOR LOCAL CULTURE PRESERVATION: INTRIGUING FAIRY TALES - Rochmiyati, Siti; Ghozali, Imam; Tiasari, Luky (PEOPLE: International Journal of Social Sciences, 2020)
Fairy tales have long been used as learning materials for Indonesian as well as English subjects in secondary schools to instil and preserve local wisdom and culture in addition to enhancing students’ linguistic competence. Based on classroom observation and interview, current practices in schools show that learning activities developed out these materials revolve around students’ involvement in reading, comprehending, appreciating, and identifying moral stories of the tales, be it orally and or in written form. Through R & D procedure, involving several junior high school students in Yogyakarta Special Region (DIY) and Central Java (Jateng), a digital media called “SoON” (Story on Odyssey Naturally) was used to develop those tales into more interactive and cognitively engaging learning materials (Littleyoung, 2015). Learning activities involve students not only to find information, retell, and identify moral story but further to enhance their soft skills and creativity through responding to the tales depending on students’ creativity. During the tryout, it was observed that the students were occupied doing all activities. Their high enthusiasm was observed in the last activity in which they got space/freedom to express themselves/their dreams. From students’ worksheet, it could be inferred that the resulting materials were also effective in exercising students’ creativity, and were effective as a means of character education. Based on the findings, the researchers contended that more folklore materials need to be converted into more innovative and interactive digital materials which are effective model not only for their preservation but for richer educational values.